Analisis Kualitas Pelayanan Dalam Penerbitan Surat Keterangan Catatan Kepolisian (SKCK) di Polres Prabumulih - Suryadinata, Suryadinata; Hendarso, Yoyok; Agus, Azwar (Mahesa Research Center, 2023)
This article or writing aims to analyze the quality of service in issuing SKCK at Prabumulih Police. The problem focuses on the quality of SKCK publishing services. In order to approach this problem, a theoretical reference from the concept of service quality according to Zeithaml (2010) was used to start the service dimensions in the Public Service Office of the Prabumulih Police Intelligence and Security Unit. Data was collected through questionnaires, observations and documentation studies, then analyzed using the Weight Mean Score (WMS). The research subjects were respondents who managed SKCK at the Prabumulih Police Station. This study concludes that the Validity Test shows that all statements are valid with a calculated r value that is capable. The average quality of SKCK services at the Prabumulih Police Station ranges from 3.32 to 4.91, indicating respondent satisfaction in the answer range of 3.01 – 4.00. Factors such as ease of access and communication between officers are considered quite good, although there are still obstacles related to understanding the importance of the application. However, the officers' efforts to provide services according to the Prabumulih Police motto were considered to be quite good.